PROFIL PEMECAHAN MASALAH POLYA MATEMATIKA SISWA KELAS VIII SMP NEGERI 6 PALU PADA MATERI STATISTIKA DITINJAU DARI TINGKAT EfFIKASI DIRI - Nurul Alfahira; Mustamin Idris; Pathuddin Pathuddin (Universitas Tadulako, 2025)
This study aims to describe the Polya's mathematical problem-solving profile of Grade VIII students at SMP Negeri 6 Palu on statistics material reviewed from self-efficacy level. This research is a descriptive study using a qualitative approach. The subjects of this study were three Grade VIII F students at SMP Negeri 6 Palu, each representing high, moderate, and low self-efficacy levels. The research data were obtained using questionnaires, tests, and interviews. The results of this study indicate that: (1) The subject with high self-efficacy:On indicator I, the subject was able to state the information known and asked;On indicator II, the subject was able to plan problem solving by applying formulas;On indicator III, the subject was able to solve problems according to the previously made plan by considering known factors;On indicator IV, the subject rechecked the answers and verified the calculation results.(2) The subject with moderate self-efficacy:On indicator I, the subject was able to state the information known and asked;On indicator II, the subject did not write the mean formula but was able to solve the given problem;On indicator III, the subject was able to solve the given problem according to the previously made plan;On indicator IV, the subject forgot to recheck the final answer.(3) The subject with low self efficacy:On indicator I, the subject was able to state the information known and asked; On indicator II, the subject did not know the plan to be used to solve the problem, did not know the mean formula, and misused the formula to solve the median; On indicator III, the subject was unable to solve part a and b of the problem due to difficulty with high multiplication calculations, but was able to determine the mode of the data;On indicator IV, the subject did not recheck the answers because they were unsure of their answers. Keywords: Problem Solving Profile, Statistical Material, Self-Efficacy